Allostatic load as predictor of mortality: a cohort study from Lolland-Falster, Denmark - Stig Egil Bojesen; Elsebeth Lynge; Christina Ellervik; Randi Jepsen; Neda Esmailzadeh Bruun-Rasmussen; George Napolitano; Knud Rasmussen; Christian Christiansen (BMJ Open)
Objectives The purposes of the present study were to determine the association between (1) 10 individual biomarkers and all-cause mortality; and between (2) allostatic load (AL), across three physiological systems (cardiovascular, inflammatory, metabolic) and all-cause mortality.Design Prospective cohort study.Setting We used data from the Lolland-Falster Health Study undertaken in Denmark in 2016–2020 and used data on systolic blood pressure (SBP) and diastolic blood pressure (DBP), pulse rate (PR), waist–hip ratio (WHR) and levels of low-density lipoprotein cholesterol (LDL-c), high-density lipoprotein cholesterol (HDL-c), triglycerides, glycated haemoglobin A1c (HbA1c), C-reactive protein (CRP) and serum albumin. All biomarkers were divided into quartiles with high-risk values defined as those in the highest (PR, WHR, triglycerides, HbA1c, CRP) or lowest (HDL-c, albumin) quartile, or a combination hereof (LDL-c, SBP, DBP). The 10 biomarkers were combined into a summary measure of AL index. Participants were followed-up for death for an average of 2.6 years.Participants We examined a total of 13 725 individuals aged 18+ years.Primary outcome measure Cox proportional hazard regression (HR) analysis were performed to examine the association between AL index and mortality in men and women.Results All-cause mortality increased with increasing AL index. With low AL index as reference, the HR was 1.33 (95% CI: 0.89 to 1.98) for mid AL, and HR 2.37 (95% CI: 1.58 to 3.54) for high AL.Conclusions Elevated physiological burden measured by mid and high AL index was associated with a steeper increase of mortality than individual biomarkers.